Comparison of shear bond strength of the stainless steel metallic brackets bonded by three bonding systems - Mehdi Ravadgar; Valiollah Arash; Hamid Pachenari (Babol University of Medical Sciences, 2013)
Introduction: In orthodontic treatment, it is essential to establish a satisfactory bond between enamel and bracket. After the self-etch primers (SEPs) were introduced for the facilitation of bracket bonding in comparison to the conventional etch-and-bond system, multiple studies have been carried out on their shear bond strengths which have yielded different results. This study was aimed at comparing shear bond strengths of the stainless steel metallic brackets bonded by three bonding systems. Methods: In this experimental in vitro study, 60 extracted human maxillary premolar teeth were randomly divided into three equal groups: in the first group, Transbond XT (TBXT) light cured composite was bonded with Transbond plus self-etching primer (TPSEP); in the second group, TBXT composite was bonded with the conventional method of acid etching; and in the third group, the self cured composite Unite TM bonding adhesive was bonded with the conventional method of acid etching. In all the groups, Standard edgewise-022 metallic brackets (American Orthodontics, Sheboygan, USA) were used. Twenty-four hours after the completion of thermocycling, shear bond strength of brackets was measured by Universal Testing Machine (Zwick). In order to compare the shear bond strengths of the groups, the variance analysis test (ANOVA) was adopted and p≤0.05 was considered as a significant level. Results: Based on megapascal, the average shear bond strength for the first, second, and third groups was 8.27±1.9, 9.78±2, and 8.92±2.5, respectively. There was no significant difference in the shear bond strength of the groups. Conclusions: Since TPSEP shear bond strength is approximately at the level of the conventional method of acid etching and within the desirable range for orthodontic brackets shear bond strength, applying TPSEP can serve as a substitute for the conventional method of etch and bond, particularly in orthodontic operations.